2002
DOI: 10.1081/jdi-120015662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gentamicin, Lipopolysaccharide, and Contrast Media on Immortalized Proximal Tubular Cells

Abstract: Aminoglycosides are widely used in the treatment of gram-negative bacterial infections. Gentamicin (GE) acts mainly in proximal tubular cells, where it is uptake via organic anion transport system and it induces a high incidence of nephrotoxicity, which is characterized by tubular necrosis [5] leading to acute renal failure in 10 to 50% of patients. Gram-negative bacteria has lipopolysaccharide (LPS) which is an endotoxin that cause renal damage. [1] Moreover, many patients are undergone exams using radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…Additionally, the present study revealed marked significant increase in urinary KIM-1 in gentamicin treated group as compared to control group. These results agreed with the study of Cunha and Schor (2002) who illustrated that, in the dose-response study, urinary KIM-1 and kidney KIM-1/Havcr1 mRNA expression are very sensitive to the renal injury produced by gentamicin. These results may be explained by the fact that gentamicin accumulates in the epithelial cells of renal proximal tubules, leading to structural changes and functional impairments of the plasma membrane, mitochondria, and lysosome (Ali, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the present study revealed marked significant increase in urinary KIM-1 in gentamicin treated group as compared to control group. These results agreed with the study of Cunha and Schor (2002) who illustrated that, in the dose-response study, urinary KIM-1 and kidney KIM-1/Havcr1 mRNA expression are very sensitive to the renal injury produced by gentamicin. These results may be explained by the fact that gentamicin accumulates in the epithelial cells of renal proximal tubules, leading to structural changes and functional impairments of the plasma membrane, mitochondria, and lysosome (Ali, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Experimental animal studies performed in vivo and in vitro have suggested that iodinated contrast drugs can induce caspase-mediated apoptosis of tubular epithelial cells 57. Activation of shock proteins and concurrent inhibition of cytoprotective enzymes and prostaglandins may also cause contrast drug-induced apoptosis 70,71…”
Section: Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…Studi su animali, sia in vivo che in vitro, suggeriscono che i MC iodati possono causare direttamente un'apoptosi, mediata dalle caspasi, delle cellule tubulari renali (93). L'apoptosi indotta dai MC può essere dovuta alla attivazione di proteine shock e alla concorrente inibizione di enzimi citoprotettivi e prostaglandine (94,95). Questo tipo di ricerche sperimentali può consentire di trovare i mezzi per contrastare la citotossicità dei MC sull'epitelio tubulare (96).…”
Section: Citotossicità Dei MCunclassified